Application of Two Neutral Mspl DNA Polymorphisms in the Analysis of Hereditary Protein C Deficiency - Reitsma, P H; te Lintel Hekkert, W; Koenhen, E; van der Velden, P A; Allaart, C F; Deutz-Terlouw, P P; Poort, S R; Bertina, R M (Thrombosis and Haemostasis, 1990)
Screening of restriction erzyme digested DNA from normal and protein C deficient individuals with a variety of probes derived from the protein C locus has revealed the existence of two neutral MspI polymorphism. One polymorphism (MI), which is located ≈7 kb upstream of the protein C gene, has allelic frequencies of 69 and 31%, and was used to exclude extensive gene deletions as a likely cause of type I protein C deficiency in 50% of cases in a panel of 22 families. Furtherrnore, the same polymorphism has been used in 5 doubly affected individuals establishing compound heterozygosity in 3 of these.The second, intragenic, polymorphism (MII) has allelic frequencies of 99 and 1% in the normal population. The frequency of the rare allele of this RFLP was with 7% much higher in a panel of 22 Dutch families with protein C deficiency. Interestingly, in all three probands that were heterozygous for MII the rare allele of MII coincided with a point mutation that leads to a stop codon in amino acid position 306 of the protein C coding sequence. This mutation may account for 14% of the protein C deficient individuals in The Netherlands.